Karakteristik Aspal Karet Dengan Penambahan Antioksidan Trimethyl Quinoline - MS, Frasucia Aquaviva; Irdoni, Irdoni; Bahruddin, Bahruddin (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Rubber asphalt modifications are used to produce asphalt roads that are more resistant to high traffic loads and extreme climate change. Natural rubber used can be latex, solid rubber or used rubber. This research aims to determine the characteristics of rubber asphalt with the addition of the antioxidant trimethyl quinoline. In this study the asphalt used is a type of asphalt pen 60/70 Pertamina. Rubber asphalt modifications are made with crepe rubber with asphalt at a mixing temperature of 160˚C for 30 minutes. Crepe Rubber ratios vary 8%, 10% and 12% and the addition of antioxidants TMQ 1%, 2% and 3%. Modification of Rubber Asphalt in accordance with the requirements of Bina Marga General Specification 2012. Rubber asphalt test results showed decreased weight loss and penetration, while mushy spots increased. Based on the results of the study the addition of 10% crepe rubber and 2% TMQ is the most optimal condition with penetration of 68.7 dmm, mushy point 55.45°C and weight loss of 0.059% which is the test result according to the standard. Keywords : asphalt rubber, crepe rubber, penetration, softening point, antioxidant